Strategic Choice Development Using SWOT Analysis: Diversification Strategy of Batik Creative Industry in Blora, Indonesia - Widjajanti, Kesi; Sugiyanto, Eviatiwi Kusumaningtyas; Widyaevan, Dea Aulia; Sari, Anisa Rachma (Journal of Economic Education, 2023)
Diversification is a strategic choice to improve company competitiveness sustainably. This paper explores strategies and suggests a suitable diversification strategy for micro, small, and medium enterprises (MSME) on a theoretical concentration and resource-based view.. Blora batik creative industry in Central Java, Indonesia, is selected as a case study. We use descriptive analytic derived from quantitative SWOT framework by combining matrix from Internal Factor Analysis (IFAS) and External Factor Analysis (EFAS). We collect data from field surveys and study literature. Respondents are selected purposively based on a result from a focus group discussion (FGD). This paper finds that Blora batik has both positive IFAS and EFAS scores, 0.42 and 0,26, respectively. These indicate Blora Batik has a strong positional value in "quadrant I", which means this industry has suitable strength to exploit opportunities.. Diversification strategy options proposed in this research can help owners and managers of micro, small and medium enterprises to expand the diversity of their markets and products. This study can also be used as a consideration for the government in implementing policies to empower the Batik creative economy through the MSME diversification strategy